The Interplay Between Financial Markets and Economic Growth - Distia, Maharani (Advances in Economics & Financial Studies, 2023)
This study aims to investigate the relationship between financial markets and economic growth, focusing on the influence of different dimensions of financial market development. Specifically, it seeks to understand how institutional quality and contextual factors moderate this relationship. The study conducts a comprehensive review of theoretical and empirical literature on financial markets and economic growth. It analyzes specific dimensions of financial market development, such as banking sector depth and stock market liquidity, using empirical analysis. Additionally, it explores the moderating role of institutional quality, financial stability, and other contextual factors. The analysis reveals a robust positive correlation between the depth and efficiency of financial markets and economic growth. Countries with well-developed financial markets tend to experience higher levels of economic growth. Moreover, institutional quality, including strong legal frameworks and political stability, plays a critical role in shaping this relationship. Financial stability also emerges as a determinant of sustained economic growth. The findings underscore the importance of prioritizing financial market development and institutional reform to foster sustainable economic growth. Policymakers should focus on enhancing financial infrastructure and governance to unlock the full potential of financial markets for economic development. These insights carry significant implications for policymakers, investors, and stakeholders striving to promote inclusive and sustainable economic growth.